The Effect of Qris Use, Product Variation, and Working Hours on The Income of Souvenir MSMEs in The Sanur Tourist Area - I Komang Suamba; Made Heny Urmila Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Economic development plays a crucial role in improving community welfare, particularly through the tourism sector and the empowerment of Micro, Small, and Medium Enterprises (MSMEs). Bali, as a leading tourist destination, significantly contributes to the regional economy through this sector. Sanur Beach in Denpasar City, which supports Bali's tourism industry, hosts numerous souvenir MSMEs that contribute to local economic activities. However, the COVID-19 pandemic has led to a decline in tourist arrivals, adversely affecting the income of souvenir MSME operators. This study aims to analyze the influence of QRIS usage, product variation, and working hours on the income of souvenir MSMEs at Sanur Beach. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to 70 MSME operators in the area. The data were analyzed using multiple linear regression analysis. The results indicate that QRIS usage, product variation, and working hours simultaneously have a significant effect on MSME income. Individually, each of these variables—QRIS usage, product variation, and working hours—positively influences income. This study concludes that digital innovation through QRIS payment systems, product diversification, and extended working hours are key factors in enhancing the income of MSMEs in the tourism sector. The implications of these findings highlight the importance of payment digitalization, improving product appeal, and optimizing operational hours for MSMEs to attract tourists.